Evaluation of Blended Irrigation Schemes: A Micro-Level Decadal Study of Shrigonda Tahsil in Drought Prone Western Maharashtra, India - Manojkumar Popatrao Devne; Ganesh Madhukar Dhawale; Jyotiram More; Mundhe Nathuram Nitin (Indonesian Journal of Geography, 2020)
The qualitative parameters of development of a quantitatively increasing population for a resource stressed country like India, is dependent on the sustainability of food availability. Agriculture remains to be a backbone of the economy and food supply. Agriculture, however, in many parts of India, even today, remains to be rain-fed. Recent efforts at the government level, Centre and State, have helped to bring a significant amount of land, initially under rain-fed agriculture, to under irrigation of various types. These varied types of irrigation change regionally; on various agro-factors. Source of water resources to be used for irrigation in the respective climatic sub-regions and the subsequent crop cultivated in the respective region are just a few primary factors controlling the effectivity of the type of irrigation method used. Irrigation requires technological inputs, which, in turn, requires financial expenses that need to be under the significant agro-factors mentioned above. Governments at the Centre and State levels; have been continuously making efforts to support irrigation practices through direct and indirect supportive schemes. These schemes have their positive, and at times, negative impact on the local agriculture at a micro-level. Agriculture is a state subject in India. The Centre does provide finance for various agricultural projects as well. Micro-irrigation has been and will play an essential role in the future in India. Ever since 1992, the government has been taking initiatives in micro-irrigation. These have eventually transpired into schemes, i.e., Centrally Sponsored Scheme (CSS) in 2006, later upgraded to the National Mission on Micro Irrigation (NMMI) implemented since 2013-14 and subsequently National Mission for Sustainable Agriculture. The present study is an attempt to evaluate such 'State' (Central and State Governments)sponsored irrigation programs on agricultural practices at a micro level, over a decade (2005-2016). The study area identified for the same is a tahsil in the Ahmednagar district of Western Maharashtra. What is significant is that, the said tahsil Shrigonda; lies in the drought-prone region and that there have been cyclic variations in the rainfall, and the various agriculture crops cultivated through the last decade. State Government-sponsored schemes are seen to have been blended with Central Government schemes by the local farmers to achieve sustainability of crops. The effects of the same, on the cycle of products, is worth an observation.Human factors also play an equally important role while using the developing Technology of micro-irrigation. Farmers try-and-test various crops with the respective Micro-irrigation technique, in the respective agro-climatic regions, particularly when the source of water is not assured in the drought-prone area.  Subsequent allied government schemes (farm ponds), the market value of the product, and perishability or shelf-life of the products also play a significant role in the choice of crop. The success of the micro-irrigation schemes will, however, be dependent on the effective delivery mechanism through close coordination among all the tiers of government and capacity building of beneficiaries.